Heart rate and blood pressure responses during hypoxic cycles of a 3-week intermittent hypoxia breathing program in patients at risk for or with mild COPD - Faulhaber, Martin (Int J Chron Obstruct Pulmon Dis, 2015)
The aim of this study was to provide information on heart rate and blood pressure responses during a 3-week intermittent hypoxia breathing program in COPD patients. Sixteen participants with COPD symptoms were randomly assigned to a hypoxia or control group and completed a 3-week intermittent hypoxia breathing program (five sessions per week, each consisting of three to five breathing cycles, each cycle lasting 3–5 minutes with 3-minute breaks between cycles). During the breathing cycles, the hypoxia group received hypoxic air (inspired fraction of oxygen 15%–12%), whereas the control group received normal air (sham hypoxia). During the breaks, all participants breathed normoxic room air. Arterial oxygen saturation, systolic and diastolic blood pressure, and heart rate were measured during the normoxic and hypoxic/sham hypoxic periods. For each breathing cycle, changes from normoxia to hypoxia/sham hypoxia were calculated, and changes were averaged for each of the 15 sessions and for each week. Changes in arterial oxygen saturation were significantly different between groups in the course of the 3 weeks (two-way analysis of variance for repeated measures), with post hoc differences in weeks 1, 2, and 3. During the course of the intermittent hypoxia application, no between-group differences were detected for blood pressure or rate pressure product values. Changes in heart rate were significantly different between groups in the course of the 3 weeks (two-way analysis of variance for repeated measures), with post hoc differences only in week 3. Averages over all 15 sessions were significantly higher in the hypoxia group for heart rate and rate pressure product, and tended to be increased for systolic blood pressure. The applied intermittent hypoxia breathing program resulted in specific and moderate heart rate and blood pressure responses, and did not provoke a progressive increase in blood pressure during the hypoxic cycles in the course of the application.